2015
DOI: 10.3892/mmr.2015.4324
|View full text |Cite
|
Sign up to set email alerts
|

Sardine protein diet increases plasma glucagon-like peptide-1 levels and prevents tissue oxidative stress in rats fed a high-fructose diet

Abstract: Abstract. The current study investigated whether sardine protein mitigates the adverse effects of fructose on plasma glucagon-like peptide-1 (GLP-1) and oxidative stress in rats. Rats were fed casein (C) or sardine protein (S) with or without high-fructose (HF) for 2 months. Plasma glucose, insulin, GLP-1, lipid and protein oxidation and antioxidant enzymes were assayed. HF rats developed obesity, hyperglycemia, hyperinsulinemia, insulin resistance and oxidative stress despite reduced energy and food intakes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
(43 reference statements)
2
3
0
Order By: Relevance
“…In agreement with our previous reports (Madani et al 2012(Madani et al , 2015, we observed that fructose-fed rats display oxidative stress in both WAT and skeletal muscle after 8 weeks of experiment reflected in the elevated TBARS and LHP with respect to those of control animals. This abnormal improving glucose, insulin, insulinogenic index, HOMA-IR, HOMA-β, glucose tolerance and AUC, suggesting a protective role on complications associated with metabolic syndrome.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with our previous reports (Madani et al 2012(Madani et al , 2015, we observed that fructose-fed rats display oxidative stress in both WAT and skeletal muscle after 8 weeks of experiment reflected in the elevated TBARS and LHP with respect to those of control animals. This abnormal improving glucose, insulin, insulinogenic index, HOMA-IR, HOMA-β, glucose tolerance and AUC, suggesting a protective role on complications associated with metabolic syndrome.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the protein carbonyl increased in both tissues is suggestive of oxidative damage in addition to chemical modification, indicating that the high tissues carbonyl radicals can be produced after the attack of the • OH radical against the residues of arginine, lysine and proline (Kayama et al 2015;Radi 2018). We also found that fructose enriched diet resulted in significant reduction in nitric oxide (NO) levels in both tissues and concur with those observed in patients with MetS (Simão et al 2010) and in rats (Madani et al 2015;Mellouk et al 2012b), supposing that hyperglycemia, hyperinsulinemia and altered insulin resistance may be the cause of this effect. Furthermore, the low NO contents might be explained by a higher level of O 2 −• which can rapidly bound to NO and produce nitric peroxide (ONOO − ), oxidant molecule harmful to vascular function (Zweier et al 2011).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In DOCA-salt hypertensive rats, Melothriama deraspatana leaves extract significantly reduced LOOHs concentration in serum and tissues (liver, heart and kidney), which might be because of the presence of phenolic compounds such as coumarins and flavonoids (Chinnadurai et al, 2011). Sp reduce hydroperoxides values in heart in rats fed high-fructose diet (Madani et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Increase in vitamin C after drug administration reduced diabetes associated complications which is in accordance with (26). Vitamin C deficiency was probably due to increased turnover of ascorbic acid mediated by elevated oxidative stress (27). Exogenous administration of extract reduced stress, glucose concentration and ameliorated Vitamin C concentration in tissue.…”
Section: Discussionmentioning
confidence: 98%